Information-seeking behaviour on sexual and reproductive health among rural adolescents in Sarawak, Malaysia - Panting, Albeny Joslyn; Abdullah, Haslinda; Ismail, Ismi Arif; Roslan, Samsilah (Community Health Society Malaysia, 2018)
Background: Information-seeking behavior is among the important element in sexual and reproductive health. However, there are limited studies focused on rural adolescents in Sarawak regarding information-seeking behaviour on sexual and reproductive health. Thus, the purpose of this study is to identify sexual and reproductive health information-seeking behaviour among rural adolescents in Sarawak. Materials and Methods: Cross-sectional study was conducted involving 3 rural districts in Sarawak namely Padawan (Kuching), Kanowit (Sibu) and Suai-Niah (Miri). This study utilized multi-stage sampling frameworks and conducted from August to November 2016. Structured questionnaire in Malay language with constructs on information-seeking were modified from Cleland, Ingham and Stone (2005). Pilot study was conducted in Samarahan, Sarawak with Cronbach alpha value 0.81. The overall response rate in this study was 95% (N = 1086) and sample size for rural respondents was n=259. The data were then analyzed using SPSS version 21. Result: Result indicated that respondents obtained sexual and reproductive health information through three main sources; internet (mean = 1.12; sd = 1.44 ), peers (mean = 1.05 , sd = 1.35), and electronic media (mean = 1.01; sd = 1.35). While the level of confidence in using the various sources of sexual and reproductive health information, were health personnel (mean = 1.37; sd = 1.65), parents (mean = 1.23; sd = 1.52), internet (mean = 1.22 ; sd = 1.50). Conclusion: These findings suggested the need to utilize the strengths of these information sources regarding SRH information-seeking behaviour in developing an effective health education strategies for adolescents in Sarawak.